Semiotic Analysis of Place and Time in Poems of Badr Shakir al-Sayyab - Boezar, Razi; Mehr, Mohammad Shayegan; Husseinjanzadeh, Fariborz (Journal of History Culture and Art Research, 2017)
Abstract Place and time play an important role in Sayyab poetry that is closely related to literature and social life and this is regarded as an important element in Sayyab poetry. Thus, the purpose of this study is to investigate the time and place in poems of Badr Shakir al-Sayyab as well as his semiology in creating the comprehensive artwork. Semiology creates communicational – psychological effect on listener and puts a photographic form in mind and through verb between the speaker and the listener. Sayyab used spatial cues of aesthetic particles in poem subjects for himself. Spatial semiotics has recently come to the attention of linguistics that Swiss scientist Ferdinand de Saussure used it for symptoms of knowledge in the process of communication and exchanging the information. This study analyzes poems of Sayyab by using descriptive-analytical method from this perspective. The spatial cues help us to locatr beauty in Sayyab poetry and the treasures of intellectual knowledge that is hidden amidst his poems through the village, town and where he met with his beloved have been found out. In this study, we rely on the full poetry implementation of Badr Shakir Sayyab.